Mengantar Umat Difabel Kepada Pengenalan Iman: Katekese Sebagai Sarana Pendidikan Kristiani yang Inklusif - trisantus, trisantus; Yohanes Wilson B.Lena Meo (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
Catechesis is the main means for the Church to educate and pass on the faith to the people. However, people with disabilities often experience limited access to faith education that suits their needs. This paper discusses how catechesis can be more inclusive in guiding people with disabilities to the knowledge of faith. This study aims to: (1) identify the challenges faced by people with disabilities in attending catechesis, (2) explain the strategies and methods that can be applied in inclusive catechesis, (3) propose concrete steps for the Church in developing catechesis that is more adaptive to the needs of people with disabilities. The formulation of the problems that form the basis of this research include: first, what are the challenges faced by people with disabilities in receiving faith education? Second, how can catechesis be designed to be more inclusive for people with disabilities? Third, what is the role of the Church in supporting inclusive catechesis? With a more adaptive approach and friendly methods for people with disabilities, the Church can ensure that every believer, without exception, has the same opportunity to understand and live the Christian faith.